1989
DOI: 10.1104/pp.90.4.1279
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Cycling of Autophosphorylation of a Ca2+-Calmodulin Regulated Plasma Membrane Located Protein Kinase from Pea

Abstract: Plasma membrane vesicles from pea (Pisum sativum L.) seedlings contain an autophosphorylating calcium-activated protein kinase of relative molecular weight 18,000 (phosphoprotein 18, pp18). Pulse chase analysis revealed that pp18 autophosphorylation exhibited very rapid tumover. pp18 was the only detectable plasma membrane protein to have this property. pp18 has been highly purified by affinity chromatography and the final preparation contains peptides of relative molecular weight 67,000,48,000, and 18,000. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 18 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…When purified pea plasma membrane was incubated in vitro with [32P]ATP, we observed one protein (in this example with a molecular mass of 18 kD) to complete its phosphorylation within 15 s, whereas other proteins required 5 to 10 min before phosphorylation was apparently completed. We were able to demonstrate subsequently (Blowers and Trewavas, 1989) that this very rapid phosphorylation was the result of autophosphorylation of a protein kinase. The 70-and the 60-kD peptides may simply be protein kinases that autophosphorylate in a Ca2+-dependent manner, a possibility we are testing at present (Grimm et al, 1989).…”
Section: Discussionmentioning
confidence: 80%
“…When purified pea plasma membrane was incubated in vitro with [32P]ATP, we observed one protein (in this example with a molecular mass of 18 kD) to complete its phosphorylation within 15 s, whereas other proteins required 5 to 10 min before phosphorylation was apparently completed. We were able to demonstrate subsequently (Blowers and Trewavas, 1989) that this very rapid phosphorylation was the result of autophosphorylation of a protein kinase. The 70-and the 60-kD peptides may simply be protein kinases that autophosphorylate in a Ca2+-dependent manner, a possibility we are testing at present (Grimm et al, 1989).…”
Section: Discussionmentioning
confidence: 80%
“…It is possible that they are the result of protein kinase activity in these membrane fractions. Rapidly tuming-over kinases have been demonstrated in other plant tissues (Blowers and Trewavas, 1989;Garbarino et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…A possible regulatory function remains conceivable given the abundant expression of NDPK/Nm23 in many tumor tissues [39, 401. Further evidence for the existence of a Nm23 protein phosphotransferase activity in the cell is provided by several reports on NDPK from plants, which all show a high degree of sequence similarity to human NDPK 1411. It was reported that NDPK may act as a kind of active subunit of protein kinase complexes in pea [42,43] and sugar-cane [44]. The NDPK preparations apparently exhibited a weak serine phosphotransferase activity toward membrane proteins, which could be stimulated by Ca' ' and calmodulin.…”
Section: Discussionmentioning
confidence: 99%